Late auditory event-related potential changes after sensorimotor rhythm neurofeedback training - Stanković, Ivana; Ilić, Tihomir V.; Jeličić, Ljiljana; Subotić, Miško; Martić, Vesna; Sovilj, Mirjana; Ilić, Nela V.; Stokić, Miodrag (Vojnosanitetski pregled, 2022)
Background/Aim. Neurofeedback (NFB) is a therapeutic method based on monitoring the electroencephalogram (EEG) and providing feedback on the brain activity of subjects. The aim of the pilot study was to investigate the effect of lower-beta or sensorimotor rhythm (SMR) (12–15 Hz) NFB training on amplitudes and latencies of late auditory event-related potentials (aERP) components N100, N200, P300 in Go-No go task of auditory discrimination. Methods. Each of 9 healthy participants aged 25–40 years (4 male) had 20 daily sessions of SMR neurofeedback training. The aERP was recorded 5 times: before NFB, after 5, 10, and 20 sessions, and one month after the last session. Results. The results showed a statistically significant decrease in N100, N200, and P300 latencies at Fz, Cz, and Pz regions. No significant effect of NFB training on amplitudes of components N100, N200 and N300 was found. Conclusion. The obtained results suggest that NFB training exerts its effect on the processes of auditory cognition.